Posttraumatic Osteoarthritis Damage in Mice: From Histological and Micro–Computed Tomodensitometric Changes to Gait Disturbance. (December 2021) - Fouasson-Chailloux, Alban; Dauty, Marc; Bodic, Benoit; Masson, Martial; Maugars, Yves; Metayer, Benoit; Veziers, Joëlle; Lesoeur, Julie; Rannou, François; Guicheux, Jérôme; Vinatier, Claire
Objectives: Osteoarthritis is a painful joint disease responsible for walking impairment. Its quantitative assessment by gait analysis in mice may be a relevant and noninvasive strategy to assess the disease severity. In this study, we aimed to determine the severity of osteoarthritis at the tissular and gait levels in unilateral and bilateral posttraumatic murine osteoarthritis. Methods: Twenty-four C57BL/6 male mice were randomly assigned to 3 groups ( n = 8/group): controls, unilateral surgery, and bilateral surgery. Posttraumatic osteoarthritis was induced unilaterally or bilaterally by destabilization of the medial meniscus. Gait analysis was performed weekly with the CatWalk TM XT system until the 16th week after surgery. After animal sacrifices, histological and micro–computed tomographic assessment was performed. Results: Operated knees showed a significant increase in the histological score compared with controls ( P < 0.001). Calcified anterior medial meniscal bone volume was higher on the ipsilateral side after unilateral destabilization of the medial meniscus ( P < 0.001) and on both sides after bilateral intervention ( P < 0.01). One week after surgery, the mice mean speed decreased significantly in both operated groups ( P < 0.001 and P < 0.05). In the unilateral group, a significant increase in the contralateral hind print area appeared from week 4 to week 16. Conclusions: While bilateral destabilization of the medial meniscus induced no detectable gait modification except 1 week after surgery, unilateral model was responsible for a gait disturbance on the contralateral side. Further studies are needed to better define the place of the CatWalk TM in the evaluation of mouse models of osteoarthritis.